EDUCATIONAL TECHNOLOGIES AS A COMPONENT OF PEDAGOGICAL SKILL IN HIGHER SCHOOL - MEDVID, Liubov (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the components of pedagogical skill in higher school, namely the levels of teacher professionalism and it characteristics; the essence and list of criteria and components of the professional skill of a teacher of a higher school; educational technologies as the main tool for organizing the educational process.It is substantiated that pedagogical technologies used in higher school should have certain qualities: conceptuality, systematicity, manageability, efficiency and reproducibility. Particular attention is paid to the improvement of pedagogical skills in new realities, where a student-centered approach and the formation of general and professional competences in students of higher education, which are indicators of the quality of modern education, must be taken into account. The author notes that modern forms of organization of the educational process also dictate new technologies of the educational process, namely, interactive learning technologies, which involve the interaction of a teacher and a student of higher education.Interactive learning technologies are the organization of educational and cognitive activities, which consist in the active interaction of students with each other and the construction of interpersonal communication in order to achieve the planned result under the guidance of the teacher. It includes: group (cooperative) training as a form of training organization in small groups united by a common educational goal; frontal technologies, which involve the simultaneous joint work of the entire group of applicants; learning in the game, which allows for the development of creative professional thinking, in the process of which the applicant acquires the ability to analyze specific situations and solve new professional tasks; learning in discussion as a form of interactive learning, which is an important means of cognitive activity of applicants in the learning process.Therefore, pedagogical skill can be considered an innovative technology of pedagogical action, since it provides a link between pedagogical theory and practice and, thanks to creative search processes, helps teachers find modern and effective pedagogical technologies.
Keywords: рedagogical skill; educational technologies; student-centeredness; competencies; role-playing game; business game; case method